Preacher’s Preaching Model in Community Development in Pattongko Village, Central Sinjai District - Nursan; Mahmuddin; Arifuddin (Jurnal Mercusuar, 2022)
This research discusses the Communication of Preachers (Mubaligh) in Religious Development among the Community in Pattongko Village, Central Sinjai Sub-District. The objective of this study is to analyze the communication of preachers in religious development among the community in Pattongko Village, Central Sinjai Sub-District. This research is qualitative in nature and employs a Naturalistic approach. Primary and secondary data sources are used. Data collection methods include observation, interviews, and documentation. Data processing and analysis proceed through three stages: Data Collection, Data Reduction, Data Display, and Conclusion Drawing (Verification). The results of this research indicate that the communication of preachers in Pattongko Village encompasses initiatives to enhance people’s understanding of the existence of Allah SWT, nurture belief in Allah SWT, create a community that practices tolerance, and foster a community with disciplined, independent, responsible, and honest values. The communication ethics used by the preachers are based on communication principles in the Quran in Pattongko Village, Central Sinjai Sub-District, consisting of six principles: qaulan karima (noble words), qaulan sadida (truthful words), qaulan ma’rufa (good words), qaulan baligha (effective, open, transparent words), qaulan layyina (gentle words), and qaulan maisura (appropriate words). The implication of this research is that the gathered information can be used by the community as a reference for further research and as reading material on the communication of preachers in religious development in Pattongko Village, Central Sinjai Sub-District. Further studies are needed on the Communication of Preachers in Religious Development to provide optimal solutions. It is also important to follow up on the results of this research to ensure practical implementation beyond theoretical aspects.